A reusable microRNA sensor based on the electrocatalytic property of heteroduplex-templated copper nanoclusters. Issue 29 (11th March 2015) - Wang, Zhaoyin; Si, Ling; Bao, Jianchun; Dai, Zhihui
Abstract : Repeat detection of miRNA is accomplished by reconstruction of DNA–RNA heteroduplexes-templated copper nanoclusters on an electrode surface. Abstract : DNA–RNA heteroduplexes have been used as templates for copper nanocluster (CuNC) formation for the first time. Taking advantage of the electrocatalysis of CuNCs, quantitation of miRNA can thus be accomplished. More importantly, by simply operating several rounds of CuNC formation, repeated detection of miRNA has further been realized, which is rare in miRNA biosensors.